Linc00963 up-regulation alleviates postmenopausal osteoporosis through suppression of miR-506-3p - Qiang Li; Jian Zhao; Xiaoxia Yang; Lihua Guo; Yong Xu (Journal of Orthopaedic Surgery and Research)
Abstract Background This study aimed to investigate the regulatory effect of linc00963 on postmenopausal osteoporosis and the potential molecular mechanisms. Methods Taking MC3T3-E1 cells as the study object, a cell cycle assay was used to evaluate the effect of linc00963 on cell proliferation. mRNA levels of Runx2, OCN, collagenia-1, OPG, RANKL and RANK were detected. Dual luciferase reporter assay verified the targeting relationship between linc00963 and miR-506-3p. A postmenopausal osteoporosis rat model was established after ovariectomy in 32 Sprague-Dawley rats. The rats were divided into sham group, OVX group, linc00963 overexpression group, and blank plasmid group. The bone mineral density (BMD) of the rat femur was measured by X-ray bone densitometer. Serum linc00963 expression in rat was detected by RT-qPCR. The protein expression of ALP, and BGP in the serum of rats was detected by ELISA. Results Cell studies have shown that linc00963 alleviates postmenopausal osteoporosis by down-regulating the expression of miR-506-3p. Animal studies showed that compared with the sham group, the serum linc00963 level, BMD, serum Ca, P, LEP, SOD, and OPG levels in the OVX group were significantly decreased, while the levels of body weight, ALP, BGP, IL-6, IL-13, RANKL, and RANK were significantly increased. Compared with the OVX group, the use of linc00963 overexpression plasmid can significantly improve the above indexes and play a corresponding therapeutic effect on menopausal osteoporosis rats. Conclusion Linc00963 is involved in the pathogenesis of postmenopausal osteoporosis by up-regulating miR-506-3p and activating the OPG/RANKL/RANK pathway. Linc00963 is expected to be a potential therapeutic target for postmenopausal osteoporosis.